OsOSCA1.1 Mediates Hyperosmolality and Salt Stress Sensing in Oryza sativa - Yang Han; Yinxing Wang; Yuanjun Zhai; Zhaohong Wen; Jin Liu; Chao Xi; Heping Zhao; Yingdian Wang; Shengcheng Han (Biology, 2022)
OSCA (reduced hyperosmolality-induced [Ca2+]i increase) is a family of mechanosensitive calcium-permeable channels that play a role in osmosensing and stomatal immunity in plants. Oryza sativa has 11 OsOSCA genes; some of these were shown to complement hyperosmolality-induced [Ca2+]cyt increases (OICIcyt), salt stress-induced [Ca2+]cyt increases (SICIcyt), and the associated growth phenotype in the Arabidopsis thaliana mutant osca1. However, their biological functions in rice remain unclear. In this paper, we found that OsOSCA1.1 mediates OICIcyt and SICIcyt in rice roots, which are critical for stomatal closure, plant survival, and gene expression in shoots, in response to hyperosmolality and the salt stress treatment of roots. Compared with wild-type (Zhonghua11, ZH11) plants, OICIcyt and SICIcyt were abolished in the roots of 10-day-old ososca1.1 seedlings, in response to treatment with 250 mM of sorbitol and 100 mM of NaCl, respectively. Moreover, hyperosmolality- and salt stress-induced stomatal closure were also disrupted in a 30-day-old ososca1.1 mutant, resulting in lower stomatal resistance and survival rates than that in ZH11. However, overexpression of OsOSCA1.1 in ososca1.1 complemented stomatal movement and survival, in response to hyperosmolality and salt stress. The transcriptomic analysis further revealed the following three types of OsOSCA1.1-regulated genes in the shoots: 2416 sorbitol-responsive, 2349 NaCl-responsive and 1844 common osmotic stress-responsive genes after treated with 250 mM of sorbitol and 125 mM NaCl of in 30-day-old rice roots for 24 h. The Gene Ontology enrichment analysis showed that these OsOSCA1.1-regulated genes were relatively enriched in transcription regulation, hormone response, and phosphorylation terms of the biological processes category, which is consistent with the Cis-regulatory elements ABRE, ARE, MYB and MYC binding motifs that were overrepresented in 2000-bp promoter regions of these OsOSCA1.1-regulated genes. These results indicate that OsOSCA-mediated calcium signaling specifically regulates gene expression, in response to drought and salt stress in rice.